How do we think? - Ballard, Carol (Austin, Tex. : Raintree Steck-Vaughn, 1998)
Describes the various parts of the brain and the nervous system and how they function to enable us to think, feel, move, and remember.
Includes bibliographical references (p. 31) and index.
Booklist.
Appraisal-Science Books for Young People.
L.A. Recommended Foreign Language.
5.5
K-3
Keywords: Brain -- Juvenile literature; Nervous system -- Juvenile literature; Thought and thinking -- Juvenile literature; Brain; Nervous system; Brain; Nervous system; Thought and thinking; Thought and thinking; Brain; Nervous system